Dompet Desain Budaya Sebagai Tren Masa Kini - Ilham Amri; Immanuel Tobing; Khairani Liza; Syareefa Reihan Maryam; Osberth Sinaga (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
In the era of globalization, fashion accessories are no longer limited to functional purposes but have evolved into instruments of personal and cultural expression. Wallets, as one of the most widely used accessories, are now experiencing a shift in design orientation toward cultural values. This study aims to analyze the phenomenon of culturally designed wallets as an emerging modern trend through a comprehensive literature review. The research explores various academic and industry sources published between 2018 and 2024 to understand how cultural elements are integrated into wallet designs and how these influence consumer preferences.The study identifies three primary factors that drive consumer interest in culturally themed wallets: aesthetic value, sustainability, and innovation. Aesthetic value refers to the visual and symbolic appeal of cultural motifs, which resonate with consumers seeking uniqueness and identity. Sustainability reflects the growing awareness among younger generations—especially Millennials and Gen Z—regarding ethical consumption and the use of eco-friendly materials. Innovation in design, such as the fusion of traditional patterns with modern functionality, also plays a crucial role in maintaining market relevance.The findings suggest that culturally inspired wallets have a distinctive market niche, appealing to consumers who value both cultural heritage and modern fashion sensibilities. Moreover, these products support the preservation and promotion of local culture in the context of global commerce. This study contributes to the growing body of literature on culture-based product development and provides insights for stakeholders in the creative industry to enhance product innovation, cultural storytelling, and market competitiveness in the global fashion landscape.